Komisaris Independen, Komite Audit, Struktur Modal, Profitabilitas dan Harga Saham - I Made Dwi Udayana; I Putu Miartana (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTThe aim of this study is to investigate the influence of independent commissioner, audit committee, capital structure and profitability to stock price. This study uses secondary data in the form of financial statement and stock price of the company period 2013 to 2016. The population in this study are all companies that have registered in the BUSINESS-27 index during 2013 to 2016 and publish financial statements in 2013 to 2016. The total sampling technique is used in the selection of samples, so that the number of samples obtained equal to the total population of 38 companies. The analysis technique used is path analysis. The results of this study indicate that independent commissioners, audit committees, capital structure and profitability have no effect on stock prices. Independent commissioners and audit committees have a significant positive effect on profitability, while capital structure has a significant negative effect on profitability.